Long-Acting Morphine Following Hip or Knee Replacement: A Randomized, Double-Blind, Placebo-Controlled Trial - Shirley L Musclow; Tabatha Bowers; Hanna Vo; Mark Glube; Thong Nguyen (Pain Research and Management)
BACKGROUND: Patients undergoing total hip or knee replacement surgery experience unmanaged pain during postoperative physiotherapy sessions. It was theorized that a baseline opioid would improve pain management.